Development of a Problem-Based Learning Module Integrated with the Ethnochemistry of the Sasak Tribe to Improve Students’ Scientific Literacy - Reni Andriani Andriani; Muhammad Shohibul Ihsan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to develop a problem-based learning module integrated with the ethnochemistry of the Sasak tribe to improve students’ scientific literacy that is feasible, practical, and effective. This type of research is development research, Research and Development (R&D), based on the development model of Nieveen, N., which includes the stages of preliminary research, prototyping, summative evaluation, and systematic reflection and documentation. The subjects of this study were students from two private senior high schools located in East Lombok. The large-scale trial used a pretest-posttest control group design. The results of the study showed that the average feasibility score for the problem-based learning module integrated with the ethnochemistry of the Sasak tribe was 78.5 in the feasible category, and the scientific literacy instrument obtained a score of 82.6 in the very feasible category. The use of the ethnochemistry learning module for the Sasak tribe received an average score of 80.3 from teachers and students, with very practical criteria. The ethnochemistry learning module for the Sasak tribe was effective in improving students’ scientific literacy, with scores for X increasing from 51 to 84.52 and for Y increasing from 44 to 75.8, with average N gains of 0.68 and 0.57 in the medium category. These results indicate that the problem-based learning module, integrated with the ethnochemistry of the Sasak tribe and developed to improve students’ scientific literacy, meets the criteria of feasibility, practicality, and effectiveness